Digitalization of volleyball match system material: Learning innovation at the faculty of sports science, university of Medan - Kasih, Indra; Widiyaningsih, Onyas; Faridah, Eva; Simatupang, Nurhayati; Sinulingga, Albadi; Siregar, Samsuddin (Edelweiss Applied Science and Technology, 2024)
The use of digital technology has been proven to help implement sports practices more effective and efficient. However, no digital system in Indonesia has been developed specifically for volleyball matches. Therefore, this study aims to develop a digital volleyball match system. This research was conducted at the Faculty of Sport Science, State University of Medan, in the Physical Education, Health and Recreation Study Program. The research was conducted using the ADDIE development model, which includes the analysis, Design, Development, Implementation, and Evaluation stages. The data collection techniques used in this study were questionnaires and documentation. This study's development data collection instruments consisted of questionnaires for students, questionnaires for implementing media and material expert validation, and cameras for documentation. The data obtained from the questionnaire were analyzed quantitatively. Based on the data collected and analyzed, it was found that the digital volleyball match system developed was categorized as good from the material and media expert test. Furthermore, after being revised according to input from experts, from the implementation carried out at the small group trial stage, it was found that the digital media developed was categorized as good. After being revised again, based on the results of the large group trial, it was found that the developed digital media was categorized as very good. From these results, it can be concluded that the media is ready to be used in learning the volleyball administration system.